Etnografia entre as mulheres Kokama sobre o cultivo e uso de plantas medicinais - Melo, Greiciane dos Santos (Brasil, 2023)
This work aims to carry out an ethnography of the use of medicinal plants by the Kokama of the Community of Santo Antônio, in the municipality of Benjamin Constant - AM, aiming at the oral reports of nine interlocutors on how they cultivate and where and how they learned to carry out the practices of healing through home remedies prepared from medicinal plants, which help in the reflections presented here. This study is supported by the ethnographic research method, with a qualitative approach. The research provided a closer relationship with the community members, getting to know even more about each one's day-to-day life, finding out their knowledge about plants and how they cultivated plants in their own backyards and how they prepared home remedies. The community trusts a lot in the effectiveness of these home remedies, where any illness immediately runs in search of these plants. And it is of great importance to pass on this knowledge, however, using medicinal plants with conscience.